Cerebral tissue oxidative ischemia-reperfusion injury in connection with experimental cardiac arrest and cardiopulmonary resuscitation: Effect of mild hypothermia and methylene blue - Wiklund L.; Patnaik R.; Sharma A.; Miclescu A.; Sharma H.S. (My University, 2025)
The present investigation is an expansion of previous studies which all share a basic experimental protocol of a porcine-induced cardiac arrest (CA) of 12 min followed by 8 min of cardiopulmonary resuscitation (CPR), different experimental treatments (immediate as well as postponed induced mild hypothermia and administration ofmuch or less cool intravenous fluids), and a follow-up period of 3 h after which the animals were sacrificed. Another group of animals was studied according to the same protocol after 12-min CA and “standard CPR.” After death (within 1 min), the brains were harvested and frozen in liquid nitrogen awaiting analysis. Control brains of animals were collected in the same way after short periods of untreated CA (0 min, 5 min, and 15-30 min). Previous studies concerning chiefly neuropathological changes were now expanded with analyses of different tissue indicators (glutathione, luminol, leucigenin, malonialdehyde, and myeloperoxidase) of cerebral oxidative injury. The results indicate that a great part of oxidative injury occurs within the first 5 min after CA. Immediate cooling by administration of much intravenous fluid results in less cerebral oxidative injury compared to less intravenous fluid administration. A 30-min postponement of induction of hypothermia results in a cerebral oxidative injury comparable to that of “standard CPR” or the oxidative injury found after 5 min of untreated CA. Intravenous administration of methylene blue (MB) during and immediately after CPR in combination with postponed cooling resulted in no statistical difference in any of the indicators of oxidative injury, except myeloperoxidase, and glutathione, when this treatment was compared with the negative controls, i.e., animals subjected to anesthesia alone. © The Author(s) 2017.